La patología forense para determinar si un caso es homicidio o suicidio (2014)
As forensic pathology science that studies the causes and how it happened death for the case study also important tools such as interviews with people close to the victim, videos wherever possible with the aim of detecting hours used admission to place, time spent on self and others and that the identification is performed by expert witnesses in identifying people, because as the scene is posed by the offender to do to see that the person had committed suicide, plus Identifying actions such as promiscuity he always refused, as stated in the interviews given by friends and neighbors, and also items that appear on the scene as Diazepam is completely sealed bottle, which creates the assumption that the person committed the offense by the desire to go out and fix everything he forgot some important details, (and that conferences were held in the diploma is interesting to quote the following) ""the perpetrator leaves or takes something almost most scenes ""the key is to be very skilled to locate and in this case and left several evidences to prove murder, it also carries as important as the murder weapon and also saves element, and that all these elements evidence could be collected through the report of forensic medicine in which he could point out that indeed there is coincided with flask and consumption of alcohol in blood count lake, as this last was the main question that arose why was a lake blood count if according to the position where the body was found and also having observed against that element may have hit not found that none had a bloodstain"